PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR - Ena Noveria, Wella Afri Mandasari, Atmazaki, (Universitas Negeri Padang, 2017)
The purpose of this study is (1) to determine the level of skills to teks procedur tales of students VIII MTsN Tiku without using project based learning media images. (2) to find out the skill level teks procedur the students of the country VIII class MTsN Tiku by using assisted project based learning images series. (3)analyze the effect of applications of project based learning model of media assisted to teks procedur skills li tale students VIII MTsN Tiku. This type of research is quantitative with quasi-experiment methode. The use of project based learning model media images berrei affect the skills to teks procedur tales students VIII MTsN Tiku. Kata kunci: pengaruh, model project based learning berbantuan media gambar, menulis teks prosedur